2020
DOI: 10.1038/s41559-020-01303-0
|View full text |Cite
|
Sign up to set email alerts
|

Tropical and Mediterranean biodiversity is disproportionately sensitive to land-use and climate change

Abstract: Global biodiversity is undergoing rapid declines, driven in large part by changes to land use and climate. Global models help to understand the consequences of environmental changes for biodiversity, but tend to neglect important geographical variation in the sensitivity of biodiversity to these changes. Here we test whether biodiversity responses to climate change and land-use change differ among biomes (geographical units that have marked differences in environment and species composition). We find the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(173 citation statements)
references
References 66 publications
(115 reference statements)
8
135
0
3
Order By: Relevance
“…2A), while being lower in temperate and boreal ecoregions. These results align with previous studies that reported a high sensitivity of tropical forest assemblages to even low levels of human pressure (Gibson et al, 2011; Barlow et al, 2016; Newbold et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…2A), while being lower in temperate and boreal ecoregions. These results align with previous studies that reported a high sensitivity of tropical forest assemblages to even low levels of human pressure (Gibson et al, 2011; Barlow et al, 2016; Newbold et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…We recorded an elevated extinction risk for some taxon-rich genera, such as Allium , Centaurea , Hieracium , and Limonium , for which Greece represents their diversification or diversity center (for at least some of their sections—e.g., [ 83 , 84 ]). The majority of these taxa occur either in coastal or lowland areas, where land-use change due to human activities has been intensifying during the past two decades ( (accessed on 3 September 2020)); [ 85 , 86 ]) leading to habitat loss and degradation, two major factors related to increased extinction rates [ 7 , 12 , 22 ], especially in the Mediterranean [ 85 ]. Currently, only one taxon ( Isoetes heldreichii ) is presumably extinct in Greece [ 87 ], while other taxa that were considered extinct, were recently rediscovered (e.g., [ 88 , 89 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are always exceptions to the rule; for example, although most of the shifts observed have been northwards and uphill, there are few cases where plants followed in the opposite direction (see [19,21]). This has led to an increase in biotic homogenization all over the globe, since many range-restricted species are experiencing range contractions, while widespread and alien species are gaining ground, due to the intensifying effects of both climate and land-use change [54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%